Analisis Perilaku Kewirausahaan dan Pengaruhnya Terhadap Keberhasilan Usaha Pada Usaha Kecil Menengah Bawang Goreng Di Kecamatan Dringu, Kabupaten Probolinggo - Arif Syaifudin (Fakultas Ekonomi Universitas Panca Marga, 2020)
This research attempts to knowing how much the influence of entrepreneurship behavior towards the success of business and knowing the succes business of entrepreneurship bawang goreng enterpreise at Dringu Subdistrict Probolinggo. The research utilizes descriptive quantitativeresearch. To add more, the method used in this research is explanatory survey. Independent variable (X) is the entrepreneurship behavior, whereas dependent variables (Y) is success of business. The research samples are 30 respondents who are bawang goreng entrepreneurs in Dringi Subdistrict Probolinggo. For the technique analysis, it is used simple linier regression analysis. The result of research shows that the influence of entrepreneurship behavior towards the success of business is 33%. Form the result, it can be concluded that bawang goreng entrepreneurs in Dringu Subdistrict Probolinggo should optimize entrepreneurship behavior to increase the success of their businesses. It is due to the fact that entrepreneur behavior has a positive influence towards thr success of business.